Bee fearless : dream like a kid - Ulmer, Mikaila; Stevens, Brin (G.P. Putnam's Sons, 2021)
Fifteen-year-old lemonade entrepreneur Mikaila Ulmer discusses how she became an entrepreneur at the age of four and why bee conservation became an important part of her business plan. Ulmer details how her business has taken her on "Shark Tank" and to the Obama White House, and she offers other kids tips for pursuing their passions.